Improving mosque information media based on web applications using the system development life cycle method - Rahmawati, Rahmawati (SEAN Institute, 2024)
This research is motivated by the difficulty of accessing mosque information. Starting from prayer schedules, call to prayer officers, imams, and Bilal, to information about mosque finances that should be transparent. All mosque congregations need to see where the funds are being spent, and donors also need access to see what activities have been carried out by the Al-Basfar Mosque Prosperity Council (DKM). All information is only written on the mosque's information board, finances are only made using a notebook. Mosque activities such as the Commemoration of Islamic Holidays (PHBI) only have photo documentation that is displayed on the mosque's information board, which will be replaced periodically. The purpose of this research is to create a web-based information media application for the Al-Basfar mosque in order to increase the socialization of the Mosque Prosperity Council (DKM) to worshipers and donors as well as the community in general. The first step of the method used in making this website is planning, then making a design that is approved by the Al-Basfar Mosque Prosperity Council (DKM), then the process of creating a program (scripting) using CMS ( Content Management System), after creating the program, the author carries out testing both script testing and database testing, after the trials are carried out and the website runs well, the next stage is to introduce the website to the public, worshipers and donors (promotion), the last stage is perform maintenance on the website. After this research was carried out, the resulting target outputs were web-based information media applications for the Al-Basfar mosque and National journals with ISBNs for research documents..